Can out-of-hours operating in gynaecology be reduced?. Issue 3 (September 1992) - McKee, M; Priest, P; Ginzler, M; Black, N
Abstract : Against a background of concerns about future hospital medical staffing and the safety of unsupervised operations at night, this study examines which gynaecological operations now undertaken at night may be safely postponed until the following day. In the first phase of the study, the operations taking place at night in four hospitals were identified. In the second phase a nominal group technique was used to seek the extent of agreement among professionals about the appropriateness of postponing surgery to the following day in certain circumstances. There were considerable variations between hospitals in the volume of work and the grade of staff involved. The panel concluded that most operations now performed at night should not be postponed. This study suggests that there is limited scope for postponing gynaecological operations currently undertaken at night.